La facultad del agua - Jiménez-Leitón, Mauren (Instituto Tecnológico de Costa Rica., 2011)
Water is characterized by being a source of element of life and for being an essential resource for economic and social development in a region. Costa Rica has the potential in quantity and quality to supply its territory, however, the fact that Unesco highlights by declaring that the water resources are in crisis worldwide, mainly due to its poor management, is evident in the following three aspects: The absence of a state policy on sanitation, focusing on the sustainable supply of safe drinking water and in support of healthy environments. The lack of defined roles in the institutions involved in the process. And the knowledge of the topic, limited and scattered. Seeking to address the deficiencies in knowledge and the need to appropriate it to generate improvements in the sector, the University incorporates as the carrier source of this essential tool and proposes a research center specializing in Water Resources for State-Owned of Costa Rica, so that translates into a bridge with the executing entities of the country.
Centro de Investigación especializado en el Recurso Hídrico para las Universidades Estatales
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, Escuela de Arquitectura y Urbanismo, 2011.
Keywords: Agua; Recursos hídricos; Universidades -- Costa Rica; Centros de Investigación; Arquitectura; Diseño arquitectónico; Proyectos arquitectónicos